Development of standard protocols for biofilm-biomaterial interface testing - Fabian Cieplik, DDS, DMD, PhD; Conrado Aparicio, PhD; Jens Kreth, PhD; Gottfried Schmalz, DDS, DMD, PhD (JADA Foundational Science)
The oral biofilm is associated with the most common oral diseases such as caries, periodontitis, and peri-implantitis. It is also linked to failures of dental treatment approaches (eg, direct or indirect restorations because of adjacent caries). Therefore, the development of materials with antibacterial properties is desirable. However, the design of meaningful tests to confirm such properties faces severe problems because of the complexity of the interaction of materials with the oral biofilm. Furthermore, owing to practical reasons, such tests need to be performed in vitro. In contrast, there is a need for predictive data that are comparable between different laboratories. Therefore, standardization of such tests has been advocated. The International Organization for Standardization (ISO) with its Technical Committee 106–Dentistry may be the relevant platform for this purpose. A standard (ISO 3990) is being developed for testing the antibacterial properties of dental restorative materials. This standard defines basic requirements for sample preparation, selection of bacterial strains, test methods and assessment, and reporting of results. It is considered to be the first step, and regular revisions are planned as new scientific evidence emerges. The support of the scientific communities providing multidisciplinary input is needed.